The History of 90s English Curriculum in Indonesia - Maharani, Windy Annastasia; Qamariah, Zaitun; Mirza, Akhmad Ali (Journal Of Foreign Language Learning and Teaching, 2023)
From ancient times until now, the curriculum has been a pillar in the education system. This also applies to English education. However, in Indonesia, the English curriculum in the 90's was not maximized. That is why this paper was made, namely to study history and be able to take lessons in order to develop the English curriculum to be maximized for use in the education system in Indonesia today. The method used in this research is the Qualitative Research and Library Research method, because this method is the most suitable method in historical research. In this research, it is found that Indonesia has experienced 12 curriculum changes from the 90's until now, as well as the application of English language learning, whose role changes along with the changes in the national learning curriculum in Indonesia. This article explains the history of the curriculum in Indonesia from the past to the present, especially explaining the English curriculum in Indonesia in the 90s.